The little white horse - Goudge, Elizabeth, 1900-1984. (Gregg Press children's literature series, 1980)
In 1842, newly orphaned Maria Merryweather, her governess, and dog arrive at her ancestral home in an enchanted village in England's West Country where the people's bliss is marred by a dark shadow.